2003
DOI: 10.1103/physrevlett.91.127202
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Phase Separation inLa1xSrxCo

Abstract: 59Co NMR measurements on La1-xSrxCoO3 reported here establish unequivocally, for the first time, the coexistence of ferromagnetic regions, spin-glass regions, and hole-poor low spin regions at all x values from 0.1 to 0.5. A zero external field NMR spectrum, which is assigned to the ferromagnetic regions, has a spectral shape that is nearly x independent at 1.9 K, as are the relaxation times, T1 and T2. The integrated spectral area increases rapidly with x up to x = 0.2 and then decreases slightly for larger x… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
2

Year Published

2006
2006
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(112 citation statements)
references
References 27 publications
4
104
2
Order By: Relevance
“…In addition to local distortions, any potential Na clustering may result in poorer fits to the local structure. A two phase fit including the possibility of a Na 2 CO 3 impurity was attempted, as some amount of Na 2 CO 3 was observed in solid state 23 Na NMR (see next section), though it did not improve the fit or capture the observed peak shoulder.…”
Section: Electrical Properties and Electronic Structurementioning
confidence: 99%
See 3 more Smart Citations
“…In addition to local distortions, any potential Na clustering may result in poorer fits to the local structure. A two phase fit including the possibility of a Na 2 CO 3 impurity was attempted, as some amount of Na 2 CO 3 was observed in solid state 23 Na NMR (see next section), though it did not improve the fit or capture the observed peak shoulder.…”
Section: Electrical Properties and Electronic Structurementioning
confidence: 99%
“…23 Na is a spin 3/2 quadrupolar nucleus in 100% abundance, making it an attractive nucleus to study in the materials before and 23 Na solid-state single pulse magic angle spinning NMR spectra (9.4 T, MAS at 8 kHz) showing a principle single peak corresponding to the single site in the crystal structure with a potential minor impurity on the right edge of the peak marked by (*). (c) Resistivity vs. temperature for a pressed pellet of NaPd 3 O 3 showing the highly metallic nature of this hole-doped oxide.…”
Section: Deviations From Average Structure: Compositional Heterogeneimentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, the frustration may exist in the FM region even at temperatures close to Tc so that the whole system is not in a true ferromagnetic state. In fact, a coexistence of a hole-rich ferromagnetic phase and a holepoor cluster glasslike phase have been suggested below Tc by nMR and ac magnetic studies [27,28]. Considering these results, it is tentatively suggested that the whole system is inhomogeneous at the temperature below Tc and there are some hole-poor clusters.…”
Section: Resultsmentioning
confidence: 95%